Una especie nueva de Pachyphytum (Crassulaceae) para la flora de Jalisco, México - Pérez-Calix, Emmanuel; García Ruiz, Ignacio; Cházaro Basáñez, Miguel (Instituto de Ecología, A.C., 2008)
Pachyphytum contrerasii (crassulaceae) is proposed and described here as a new species from central Jalisco, western Mexico. this taxon belongs to the section Pachyphytum Moran, on account of its imbricate bracts of the young cincinnus, of its corolla shorter than the calyx and of its the conspicuous red dot on the inner face of the corolla segments. in terms of morphology and geography the closest relative is Pachyphytum machucae i. Garcia, Glass & cházaro, from northwestern Michoacan, in addition to its geographical distribution, Pachyphytum contrerasii is separated from this species by the possession of pedicels 2-4 mm long, a corolla 3 mm long that is shorter than the pair of larger sepals, and bicolored inner face of the petals, stamens and pistil. Besides being a new species this is the first report of the genus Pachyphytum for Jalisco state.